Effect of hurricane Dean on the structural dynamics of rain forest under forest management in Quintana Roo, Mexico - Pat-Aké, Ismael; Cámara-Cabrales, Luisa Del Carmen; Ward, Sheyla; Martínez-Zurimendi, Pablo; Martínez-Sánchez, Jose Luis; Negreros-Castillo, Patricia; Sorensen, NaDine (Instituto de Ecología, A.C., 2018)
The growing tendency of human impacts and hurricanes on the rain forest of the Yucatan Peninsula has constituted a threat to their survival. This is of great relevance, considering that the management of the rain forest is a fundamental activity for its conservation and generation of income for the local populations. This scenario was the basis for the present study carried out in the rain forest of Noh-Bec, Quintana Roo, impacted by the hurricane "Dean" (2007). The purpose was to identify the factors that had influence on the magnitude of damages caused in the arboreal community, as well as the changes in its structure and composition in the period 1998-2014. For this, measurements were made in permanent sampling plots aimed at obtaining information on the main structural characteristics, species attributes and hurricane damage (1998, 2010 and 2014). The results obtained confirmed that the damage of 56.3% of the trees of different sizes of the community was the effect of the multiple association between hurricane winds, density (trees/ha) factors, species attributes and exploitation disturbances. The results also revealed changes in the structure, importance of the species and in the structural diversity of the rain forest, variations that were manifested in an initial decrease in the heights, diameters and volumes of the arboreal community (1998-2010), to subsequently undertake regeneration processes (2010-2014). The variables density (number of trees per hectare) and basimetric area, had an inverse behavior: they first increased in the first period (1998-2010), to subsequently decrease in the second period (2010-2014).